1976
DOI: 10.1007/bf01468772
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis und partielle Lipodystrophie

Abstract: The course of disease of a patient with membranoproliferative glomerulonephritis and partial lipodystrophy is described. The case is further characterized by a deficiency of C3 and C3- activator, by normal values of C4, by evidence of the nephritogenic factor, by raised fibrin degradation products and by an unselective proteinuria. The course of the glomerulonephritis runs parallel to a pronounced susceptibility to infection (at first varicella, tonsillitis and measles, later pneumonia, meningitis, encephaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…Less frequently, other infections preceded the onset of fat loss, including viral meningitis 55 , meningococcal septicemia 105 , scarlet fever 49 , gastroenteritis 16 , chicken pox 77,134 , peritonsillar abscess and mastoiditis 11 , and rheumatic fever 11 . Reaction to tetanus antitoxin 76 , minor surgical procedures such as tooth extraction 178 , tonsillectomy 119,134 , and adenoid removal 26 , as well as sunburn (Patient 34) and psychologic stress 112 have also been reported before the …”
Section: Preceding Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less frequently, other infections preceded the onset of fat loss, including viral meningitis 55 , meningococcal septicemia 105 , scarlet fever 49 , gastroenteritis 16 , chicken pox 77,134 , peritonsillar abscess and mastoiditis 11 , and rheumatic fever 11 . Reaction to tetanus antitoxin 76 , minor surgical procedures such as tooth extraction 178 , tonsillectomy 119,134 , and adenoid removal 26 , as well as sunburn (Patient 34) and psychologic stress 112 have also been reported before the …”
Section: Preceding Factorsmentioning
confidence: 99%
“…Six patients with APL and C3 hypocomplementemia have been reported to develop meningococcal meningitis 6,88,107,134,143 . On the other hand, among 84 unselected patients hospitalized for meningococcal sepsis or meningitis, only 1 patient had APL associated with low serum levels of C3 and presence of C3NeF 107 .…”
Section: Susceptibility To Infectionsmentioning
confidence: 99%
“…No erythematous lesions were present at the beginning of the medical history of either of the patients. Various authors reported an association between this form of partial lipodystrophy and other functional or structural abnormalities, such as deafness [Spranger et al, 1997], epilepsy [Laxenaire et al, 1969], nephropathy [Jeune et al, 1965;Reichel et al, 1976;Bier et al, 1978;Kraai and van Son, 1983;Chopra et al, 2000], myopathy [Palliyath and Garcia, 1982], dermatomyositis [Quecedo et al, 1996], and vasculitis [Porter et al, 2000]. In our patients, all studies and examinations were completely normal, excluding involvement of other organs.…”
Section: Discussionmentioning
confidence: 61%
“…Due to the loss of periorbital and retro-orbital subcutaneous tissue, eyes seem to be sunken and the facial expression is characteristically progeroid. Various anomalies have been reported in the affected patients: renal disorders [Jeune et al, 1965;Reichel et al, 1976;Bier et al, 1978;Kraai and van Son, 1983;Chopra et al, 2000], central nervous system abnormalities, mental retardation, and epilepsy [Laxenaire et al, 1969]. Here we describe two patients affected by the Barraquer-Simons syndrome with only facial involvement; no other structural and functional abnormalities were associated.…”
Section: Introductionmentioning
confidence: 76%
“…As for HLA in familial MPGN, various results were reported [8]. One of identical twins had MPGN and partial lipodystrophy and an HLA type could not explain MPGN in this case [14]. Clinical and pathological findings and disease course of MPGN were different among the members of a family.…”
Section: Discussionmentioning
confidence: 94%